2020
DOI: 10.1002/jgh3.12367
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in fasting insulin secretory function correlates with significant liver fibrosis in Japanese non‐alcoholic fatty liver disease patients

Abstract: Background and Aim: Non-alcoholic fatty liver disease (NAFLD) is typically associated with metabolic syndrome and diabetes, and insulin resistance is involved in its pathogenesis. However, the relationship between insulin secretion and NAFLD is unclear. We aimed to characterize the relationship between fasting insulin secretory function (ISF), evaluated using the homeostatic model assessment-beta cell function (HOMA-β) and the severity of fibrosis during NAFLD. Methods: A-β was calculated in 188 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Diabetic patients are also usually obese and have nonalcoholic hepatic fibrosis (27). Japanese scholars have found that fasting insulin secretion could decrease with the process of non-alcoholic hepatic fibrosis (28), which may be related to glucose metabolism disorder and lipid metabolism disorder caused by islet β cell dysfunction (29). Moreover, advanced HCV hepatic fibrosis is associated with insulin resistance (30).…”
Section: Results Of the Ppi Network Analysismentioning
confidence: 99%
“…Diabetic patients are also usually obese and have nonalcoholic hepatic fibrosis (27). Japanese scholars have found that fasting insulin secretion could decrease with the process of non-alcoholic hepatic fibrosis (28), which may be related to glucose metabolism disorder and lipid metabolism disorder caused by islet β cell dysfunction (29). Moreover, advanced HCV hepatic fibrosis is associated with insulin resistance (30).…”
Section: Results Of the Ppi Network Analysismentioning
confidence: 99%
“…One study in Italy demonstrated β-cell function is lowered in biopsyproven NASH patients, but not in simple steatosis subjects [18]. Norimasa et al found that in NAFLD patients, HOMA-B% was decreased with the severity of liver fibrosis [19]. However, another study in the US found that HOMA-B% was remarkably higher in NAFLD participants and in those with β-cell dysfunction, even in simple steatosis patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…26 Normal β-cell function has HOMA-β scores 60%−100% 27 ; scores <40 are considered clinically dysfunctional, 18 and those >100% indicate overwork. 28 The SUITO index determines endogenous insulin secretion in T1D patients requiring insulin injection, by FCP (ng/mL)/ (FPG−63 [mg/dL]) × 1500, with values ≥26 reportedly correlating with insulin independence. 18 The BETA-2 score 19 is updated from the BETA score, 29 quantitated by ((√FCP (nmol/L) × (1−total daily insulin dose units/kg))/((FPG (mmol/L) x HbA1c (%)) within the range of 0−42; scores ≥16.2 reportedly correlate with insulin independence in T1D 19 and PIAT 20 patients.…”
Section: Estimations Of Endocrine Function and Insulin Independencementioning
confidence: 99%